Pie Graphs - Edgar, Sherra G. (New York : Smartbook Media Inc., 2019)
This Level 2 guided reader teaches how to interpret and create pie graphs. Students will develop word recognition and reading skills while learning how to partition shares, describe parts of a whole, and represent a data set using a pie graph.
Includes questions and answers.
Keywords: Readers -- Fiction